Foraging benefits of winning intergroup encounters in colobus monkeys - Eva C. Wikberg; Sara Lucci; Emily Glotfelty; Fernando Campos; Pascale Sicotte (Primates, 2026)
Winners of aggressive intergroup encounters are often assumed to benefit from increased access to resources, but few studies have measured whether there is differential access to resources based on the intergroup outcome. To investigate whether winning intergroup encounters is associated with increased access to food, we used 13 months of data on intergroup dynamics, feeding by 61 females, and the phenology and spatial distributions of food trees from the home ranges of 8 groups of white-thighed black-and-white colobus ( Colobus vellerosus ) at Boabeng-Fiema, Ghana. Contested trees were important food species more often than expected based on the occurrence of these species in the study area. Contested trees had young leaves, fruits, and seeds more often than expected based on the presence of these plant parts on trees monitored via monthly phenology surveys. Focal females were more likely to feed on the contested tree than other trees they were in during and immediately after the intergroup encounter. Based on group scan data collected throughout the day of an intergroup encounter, the likelihood of females feeding on any food species before and during the intergroup encounter was similar regardless of the outcome. The likelihood of feeding was higher after the intergroup encounter if the group had won compared to if the group had lost. These findings indicate that groups compete over access to important food resources and winners benefit from increased access to food. Future studies should investigate whether winning intergroup encounters is associated with long-term benefits such as increased reproductive success.

Male Sexual Coercion During Mating and Infanticide Risk Increase Self-directed Behaviors in Female Black-and-White Colobus (Colobus vellerosus) - Iulia Bădescu; Charlotte St-Onge; Allyson King; Julie A. Teichroeb; Eva C. Wikberg (International Journal of Primatology, 2026)

MHC-DRB heterozygosity may increase subordinate but not alpha male siring success in white-faced capuchin monkeys (Cebus imitator) - Janet C. Buckner; Katharine M. Jack; Margaret Buehler; Amanda D. Melin; Valérie A. M. Schoof; Eva C. Wikberg; Saul Cheves Hernandez; Linda M. Fedigan; Jessica W. Lynch (Primates, 2026)

Social network dynamics, infant loss, and gut microbiota composition in female Colobus vellerosus during time periods with alpha male challenges - Shelby Samartino; Diana Christie; Anna Penna; Pascale Sicotte; Nelson Ting; Eva Wikberg (Primates, 2024)

Black-and-white pelage as visually protective coloration in colobus monkeys - Ossi Nokelainen; Sandra Winters; Zeke Rowe; Fernando A. Campos; Eva C. Wikberg; Natasha Howell; Tim Caro (Behavioral Ecology and Sociobiology, 2024)
Conspicuous coloration is often seen as the evolutionary consequence of either sexual selection or warning predators visually about prey defences, although not all conspicuous species fit this paradigm. Exceptions include several species of colobus monkeys whose black-and-white coloration, characteristic of larger colobines, has never been explained. Here, using photographs of black-and-white colobus ( Colobus vellerosus ) taken in the wild, quantitative image analysis, and vision modelling (acuity-corrected feline, chimpanzee, and raptor vision), we provide evidence that their coloration provides distance-dependent camouflage in natural forest environments. At all viewing distances, black-and-white colobus monkeys blend into their environment because of their high chromatic overlap with the background when viewed by ecologically relevant predator vision models which have low visual acuities. Additionally, for chimpanzee and felid vision, there was evidence of edge disruption at longer viewing distances. Our comparative analyses of different species of colobines do not support an association between black-and-white coloration and larger body mass or group size, but this may simply be due to the limited number of species within the family. We reason that black-and-white colobines gain visually protective coloration through background matching against felids, and also benefit through disruptive coloration against felids and chimpanzees but rely on these protective coloration mechanisms less against raptors. Significance statement Conspicuous black-and-white coloration in colobus monkeys has long eluded an evolutionary explanation. Our research, employing photographs of colobus monkeys, image analysis, and vision modelling, unveils a novel approach to this coloration. We show that in their natural forest habitats, black-and-white colobus monkeys employ distance-dependent camouflage against ecologically relevant predators with low visual acuity, blending in with the background at increasing viewing distances. In summary, the evolution of black-and-white colobus coloration appears to be related to background matching against felids, with added benefits of disruptive camouflage against felids and chimpanzees, less so to raptors, offering fresh insights into the complex interplay of coloration and survival strategies in mammals.

Should I stay or should I go now: dispersal decisions and reproductive success in male white-faced capuchins (Cebus imitator) - Eva C. Wikberg; Katharine M. Jack; Fernando A. Campos; Mackenzie L. Bergstrom; Shoji Kawamura; Linda M. Fedigan (Behavioral Ecology and Sociobiology, 2022)

Inbreeding avoidance and female mate choice shape reproductive skew in capuchin monkeys ( Cebus capucinus imitator ) - Eva C. Wikberg; Katharine M. Jack; Linda M. Fedigan; Fernando A. Campos; Akiko S. Yashima; Mackenzie L. Bergstrom; Tomohide Hiwatashi; Shoji Kawamura (Molecular Ecology, 2017)
Reproductive skew in multimale groups may be determined by the need for alpha males to offer reproductive opportunities as staying incentives to subordinate males (concessions), by the relative fighting ability of the alpha male (tug‐of‐war) or by how easily females can be monopolized (priority‐of‐access). These models have rarely been investigated in species with exceptionally long male tenures, such as white‐faced capuchins, where female mate choice for novel unrelated males may be important in shaping reproductive skew. We investigated reproductive skew in white‐faced capuchins at Sector Santa Rosa, Costa Rica, using 20 years of demographic, behavioural and genetic data. Infant survival and alpha male reproductive success were highest in small multimale groups, which suggests that the presence of subordinate males can be beneficial to the alpha male, in line with the concession model's assumptions. None of the skew models predicted the observed degree of reproductive sharing, and the probability of an alpha male producing offspring was not affected by his relatedness to subordinate males, whether he resided with older subordinate males, whether he was prime aged, the number of males or females in the group or the number of infants conceived within the same month. Instead, the alpha male's probability of producing offspring decreased when he was the sire of the mother, was weak and lacked a well‐established position and had a longer tenure. Because our data best supported the inbreeding avoidance hypothesis and female choice for strong novel mates, these hypotheses should be taken into account in future skew models.

Demographic Factors Are Associated with Intergroup Variation in the Grooming Networks of Female Colobus (Colobus vellerosus) - Eva C. Wikberg; Nelson Ting; Pascale Sicotte (International Journal of Primatology, 2015)

Vocal Repertoire of Cebus capucinus: Acoustic Structure, Context, and Usage - Julie J. Gros-Louis; Susan E. Perry; Claudia Fichtel; Eva Wikberg; Hannah Gilkenson; Susan Wofsy; Alex Fuentes (International Journal of Primatology, 2008)